Ocular vs. Cervical Vestibular Evoked Myogenic Potentials in Benign Paroxysmal Positional Vertigo: A Systematic Review and Meta-Analysis - Chen, Gang; Dai, Xiaoyan; Ren, Xiuping; Lin, Naifen; Zhang, Min; Du, Zhaolin; Zhang, Endong (Frontiers in Neurology, 2020)
Objective: To investigate whether utricular or saccular dysfunction may be primarily responsible for the pathogenesis of benign paroxysmal positional vertigo (BPPV). Materials and Methods: We performed a literature search exploring utricular and saccular dysfunction in BPPV patients through June 2020 using ocular vestibular evoked myogenic potentials (oVEMP) and cervical VEMP (cVEMP) respectively. The databases included Pubmed, Embase, CENTRAL, CNKI, Wan Fang Data, and CBM. The literatures were limited to Chinese and English. All statistical processes were conducted through software Review Manager and sub-group analysis was performed simultaneously. Results: Seventeen studies were included for meta-analysis. 11 studies were included for analysis of response rate of cVEMP versus oVEMP, and 13 for abnormal rate. The response rate of oVEMP was not significantly different from cVEMP (odds ratios (OR) =1.67, 95% confidence interval (CI) =0.99-2.80). But the abnormal rate of oVEMP was slightly higher than cVEMP statistically (OR=1.61, 95% CI=1.04-2.48). Both response rate and abnormal rate were obviously different between the subgroups adopting ACS oVEMP and BCV oVEMP. In studies adopting ACS oVEMP, the response rate of cVEMP was higher than oVEMP (OR=2.02, 95% CI=1.53-2.66), while the abnormal rate of oVEMP was higher than cVEMP (OR=1.85, 95% CI=1.42-2.40). The abnormal rate of oVEMP was also higher than cVEMP when adopting asymmetry ratio (AR) and no response (NR) as diagnostic criteria (OR=2.11, 95% CI=1.62-2.75). Conclusion: The meta-analysis reveals that utricular dysfunction may be more responsible for the pathogenesis of BPPV compared with saccular dysfunction.